Cross-Cultural Differences in Fear of Death, Emotional Intelligence, Coping with Death, and Burnout Among Nursing Students: A Comparative Study Between Spain and Portugal - Miguel Ángel Martín-Parrilla; Noelia Durán-Gómez; Maria do Céu Marques; Casimiro Fermín López-Jurado; Margarida Goes; Macarena C. Cáceres (Behavioral Sciences)
Nursing students often face emotional challenges related to death and dying, affecting their psychological well-being, emotional intelligence, and academic success. Cultural and educational factors may influence how they experience and manage these stressors. This study aimed to compare fear of death, emotional intelligence, coping with death, and academic burnout among second-year nursing students in Spain and Portugal to identify cross-cultural differences. A cross-sectional study was conducted among 174 second-year nursing students from the University of Extremadura (Spain) and the University of Évora (Portugal) during the 2023/2024 academic year. The instruments used included the Collett–Lester Brief Fear of Death Scale, the Trait Meta-Mood Scale—24 ítems, the Bugen’s Coping with Death Scale, and the Maslach Burnout Inventory—Student Survey. Descriptive statistics were calculated, and group comparisons were performed using independent samples t-tests and Welch’s t-tests, depending on variance homogeneity. A two-way ANOVA was also conducted to explore interactions between gender and nationality. The Spanish sample comprised 86 women and 21 men, and the Portuguese sample included 58 women and 9 men. The mean age across the sample was 21.5 years (SD = 4.15). No significant differences were observed in fear of death or emotional intelligence between the two groups. However, Portuguese students showed significantly better coping with death, but also higher academic burnout and cynicism. Spanish students reported greater perceived efficacy. Although emotional intelligence and death anxiety were similar, Portuguese students demonstrated stronger coping skills but experienced more burnout. This suggests that coping alone may not buffer academic stress, emphasizing the need for culturally tailored interventions to enhance emotional readiness and reduce burnout.